The Correlation Between Family Conditions and Early Reading Skills of Children Aged 5-6 Years - Joulanda, Rovica; Ainy, Nafkhah Qurrota; Romadhoniyah, Adinda Wahyu; Widiastuti, Reski Yulina; Tittandi, Nindya Alifia; Wahyuni, Sri (Universitas Sebelas Maret, 2026)
Reading ability is an important aspect of early childhood language development. The development of reading skills is influenced not only by stimulation at school but also by the family environment as the child’s first learning environment. A supportive family condition is expected to provide optimal stimulation for the development of children's reading abilities. This study aims to determine the relationship between family conditions and the reading ability of children. This research used a quantitative approach with a correlational research design. The research subjects consisted of 13 who were selected as the sample using a total sampling technique. Data were collected through an observation sheet to measure children's reading ability and a family condition questionnaire completed by parents. Data analysis used the Spearman Rank correlation test to determine the direction and strength of the relationship between variables. The results showed a correlation coefficient of 0.319 with a significance value of 0.538 (p > 0.05). These results indicate that there is no significant relationship between family conditions and children's reading ability. Although a positive relationship was found, the strength of the relationship is weak, indicating that children's reading ability may also be influenced by other factors such as learning methods at school, children's motivation, and the teacher's role in providing appropriate stimulation according to the child's developmental stage.